2022
DOI: 10.3390/nu14163260
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity Metabolic Consequences for Adolescent Bone Health

Abstract: Infancy and adolescence are crucial periods for bone health, since they are characterized by intense physical growth and bone development. The unsatisfactory acquisition of bone mass in this phase has consequences in adult life and increases the risk of developing bone diseases at more advanced ages. Nutrient deficiencies, especially calcium and vitamin D, associated with a sedentary lifestyle; lack of sun exposure; and epigenetic aspects represent some of the main risk factors for poor bone quality. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 164 publications
0
14
0
Order By: Relevance
“…6 It also appears that obesity in the form of visceral fat in particular, appears to harm bones even in the infant-juvenile phases of development, possibly raising the risk of incurring osteopenia/osteoporosis in adulthood as well as later life. 7 Thus, even if it is accepted that the presence of any excess body weight can help to build bone, there are several pathways whereby excess weight can yet pose an unanticipated bone fracture or bone damage risk at all ages. This is due in part to a possible obesity associated array of adverse inflammatory impacts on bone genes and bone cell physiology, as well as having diverse negative metabolic influences, 8 for example in cases with type 2 diabetes who are obese.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 It also appears that obesity in the form of visceral fat in particular, appears to harm bones even in the infant-juvenile phases of development, possibly raising the risk of incurring osteopenia/osteoporosis in adulthood as well as later life. 7 Thus, even if it is accepted that the presence of any excess body weight can help to build bone, there are several pathways whereby excess weight can yet pose an unanticipated bone fracture or bone damage risk at all ages. This is due in part to a possible obesity associated array of adverse inflammatory impacts on bone genes and bone cell physiology, as well as having diverse negative metabolic influences, 8 for example in cases with type 2 diabetes who are obese.…”
Section: Resultsmentioning
confidence: 99%
“…11 In addition, it appears multiple obesogenic-associated metabolic disturbances not only impact bone homeostasis, but can affect bone quality detrimentally over time because the obese person may be less mobile or inclined to move than normal weight similar age individuals. They may thus exhibit various degrees of bone fragility, that progressively impact bone cellular processes as well as various body systems, as well as contributing to alterations in local bone homeostasis and systemic metabolism 7 and metabolic disorders, 12 especially if undetected. 13 Hsu et al, 14 found that the risks of an individual acquiring osteoporosis, osteopenia, or nonspine fractures was significantly higher for subjects with a higher percentage of body fat independent of body weight, physical activity, and age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…concluded that Body mass index (BMI) was positively associated with BMD in adolescents, their study did not adjust for some factors that have been shown to affect BMD in adolescents, such as regulating serum creatinine (10) and uric acid (11), and only considered BMI and did not consider indicators of other obesity conditions, such as waist circumference (WC) and body fat mass. Katia et al (12). found that obesity negatively impacts skeletal development in adolescents, leading to underdevelopment of bone mass.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a crucial stage for forming a solid skeleton because the bones grow in size and strength ( 4 , 5 ). The acquired bone mass in this stage (especially in the years around peak height velocity) represents approximately double the amount of bone mineral that subsequently will be lost between the ages of 50–80 years ( 6 ), and it can prevent future diseases of bone fragility such as osteopenia and osteoporosis ( 7 , 8 ). Unfortunately, excess adiposity is unfavorable to bone health in childhood due to the cross-talk between adipose tissue and bone, which regulate each other reciprocally ( 9 ).…”
Section: Introductionmentioning
confidence: 99%